GAYA KEPEMIMPINAN DEMOKRATIS KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU - Yuni, Yuni Asparani; Najib, Muhammad; Ahmad, Nur Fatih; Mahfudloh, Ririn Inayatul; Qomaruddin, Qomaruddin (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Leadership is one of the important factors that can determine the success of educational institutions in achieving goals. The use of an appropriate leadership style, such as democratic leadership, can improve teacher performance and create a conducive learning atmosphere. This study aims to describe the application of democratic leadership style by the principal at SMK Miftahul Ulum Melirang and analyze its influence on teacher performance. This research was conducted with a qualitative approach using the type of field research.The results showed that: 1) Democratic leadership style is implemented through the involvement of teachers in the decision-making process, planning, and evaluation of school programs; 2) Supporting factors for the implementation of this leadership style include effective communication and collaborative work culture, while the main obstacles are lack of training and resistance to change. This study provides recommendations to improve the effectiveness of democratic leadership style in supporting educational success at SMK Miftahul Ulum Melirang.